Case reportSturge-Weber syndrome type II treated with PDL 595 nm laser - Kowalska-Brocka, Joanna; Brocki, Maciej; Uczniak, Sebastian; Uczniak, Kamila; Kaszuba, Andrzej; Jurowski, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Sturge-Weber syndrome (SWS) is rare congenital disorder presenting facial port-wine stains (PWS) eye abnormalities and cerebrovascular malformations. The frequency of SWS is estimated at 1 in 50 000. Cerebrovascular abnormalities can be responsible for seizures, hemiparesis, mental retardation and ophthalmologic abnormalities cause intraocular pressure, glaucoma. Etiopathogenesis of SWS remains elusive. We present a case of a 7-year-old girl with SWS type II. A port-wine stain involves the upper right part of half face and has been associated with glaucoma of both eyes. In the Department of Dermatology in 2009–2012 we performed 23 procedures within 2 months. We have been using PDL laser at wavelength 595 nm and very good cosmetic results were achieved. Given positive treatment effects, the laser therapy of port-wine stains is a method of selection. Port-wine stains in the course of SWS requires a large number of laser treatment.